PENGARUH KEBIJAKAN EKSPOR ROTAN INDONESIA TERHADAP KERJASAMA INDONESIA-JERMAN DALAM UPAYA PENINGKATAN DAYA SAING PRODUK ROTAN INDONESIA DI PASAR INTERNASIONAL TAHUN 2012-2015 - Widita "; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is about a international economy politics in international relations study which gives description and analyzes about The Influence of Indonesia’s Rattan Export Policy to the Cooperation Relations between Indonesia-Germany as efforts increasing the Indonesia’s rattan products competitiveness on world trades in 2012-2015 . Indonesia is one of the main produscing countries of rattan. It makes Indonesia as dominantly supplier of rattan in the world trade. To keep the equalization of rattan trades in domestic and transborder trades, Indonesian government determines the rattan export policy that reacts to the international rattan trades. One of them is Germany as the most importer in Europe.This research is expanded by mercantilism perspective, supported by international cooperation theory, decision making theory and competitive advantage theory. This research is using state analysis unit as the main actor in international relations.This research technic and solved by qualitative research methods and library research technic.The Indonesian policy of rattan export reacts to the cooperation relations between Indonesia-Germany that is formed the new cooperation of rattan sector that held to increase the quality and productivity of Indonesia rattan to be able to compete in international trades.Keywords:Rattan, Policy, Reaction, Competitiveness, Cooperation